Eosinophilic esophagitis in children under the age of 5 years: Clinical characteristics. (2nd September 2017) - Sun, Ravi W.; Bonilla‐Velez, Juliana; Pesek, Robert D.; Johnson, Adam B.; Cleves, Mario A.; Richter, Gresham T.
Abstract : Objectives/Hypothesis: To delineate clinical characteristics and treatment outcomes of eosinophilic esophagitis (EoE) in the youngest of children. Study Design: Retrospective chart review. Methods: A 7‐year retrospective chart review of children with clinicopathologic diagnosis of EoE was performed with specific analysis of patients under 5 years old. EoE was defined as the presence of symptoms of esophageal dysfunction with pathologically proven eosinophilic inflammation (≥15 eosinophils per high‐power field [EOS/HPF]) unresponsive to reflux therapy. Patient parameters and clinical results were systematically reviewed. Results: Of 558 children diagnosed with EoE, 127 (22.8%) were younger than 5 years old (mean age 2.5 years). This subgroup presented with reflux symptoms (90.1%), vomiting (86.2%), diarrhea (55.3%), liquid dysphagia (52.0%), and constipation (50.0%), whereas food impaction (1.6%) was rare. Liquid dysphagia was present at all ages but significantly more common in younger children ( P  = .0101). The most common food and environmental allergens were egg whites (39.7%), cow's milk (36.5%), peanuts (34.9%), animal dander (15.1%), and weed pollen (11.1%). Patients were managed with antireflux medication (100%), elimination diet (83.5%), and steroid medication (68.5%). After treatment, 86% of parents reported symptom improvement. Mean reduction of EOS in pos‐treatment biopsy was 33.5 EOS/HPF ( P  < .0001), and 67 patients showed histologic resolution of EoE (56.8%, P  < .0001). Conclusions: Approximately one‐quarter of children with EoE present under 5 years of age with multiple esophageal symptoms, comorbidities, and allergen‐sensitization profiles. These patients demonstrate substantial clinicohistologic improvement following therapy. Level of Evidence: 4. Laryngoscope, 128:798–805, 2018